Rapid reference review in sports medicine : pivotal papers revealed - Miller, Mark D.; Mauffrey, Cyril; Hak, David J. (Slack Incorporated, 2015)
"As medical information expands at an exponential pace, the ability to quickly identify relevant articles becomes increasingly difficult. Rapid Reference Review in Sports Medicine: Pivotal Papers Revealed by Drs. Mark D. Miller, Cyril Mauffrey and David J. Hak offers a simple way to access and review the key points from the most relevant and important published articles. With Rapid Reference Review in Sports Medicine: Pivotal Papers Revealed orthopedic trainees may be able to quickly review several articles in preparation for a morning conference presentation of patients with a specific injury, while practicing surgeons may be able to advise patients on the relative benefits of one treatment over another. Key references include: - Classic articles - Landmark articles - Up-to-date reviews - Important clinical trials Each article is formatted to include an article citation, a summation of the abstract, a summary of key points, and author commentary. This enables readers to quickly review "bottom-line" information from the most important articles and clinical trials in orthopedic sports medicine in order to effectively plan and guide treatment. Rapid Reference Review in Sports Medicine: Pivotal Papers Revealed is a great literary reference that will prove highly useful to orthopedic residents, fellows, and physician assistants"--Provided by publisher